The ANALISIS GANGGUAN SISTEM SARAF PADA ANJING DAN STRATEGI PENANGANANNYA - Sianipar, Pebry Asarona (Jurnal Sains Indonesia, 2024)
Abstract: The nervous and hormonal systems play an important role in controlling and coordinating body functions through harmonious integration as a neuroendocrine system. The nervous system, which is only found in animals, consists of neurons and glial cells that are responsible for transmitting impulses and controlling body functions. The nervous system in dogs regulates motor, sensory, and autonomic functions to support survival. However, disorders of the nervous system, such as seizures, paralysis, or disorientation, can be caused by various factors, including congenital abnormalities, trauma, infection, or degenerative diseases. A comprehensive diagnostic evaluation and systematic treatment approach are needed to determine the cause and effective therapy. Treatment strategies include medical therapy, rehabilitation, and surgical intervention in certain cases. This study aims to analyze neurological diseases in dogs including Lower Motor Neuron (LMN) disease, Canine Distemper Virus (CDV), Rabies Virus and their treatment strategies to provide insight into the management of neurological cases, support pet welfare, and increase owner awareness of prevention efforts. Abstrak: Sistem saraf dan hormonal berperan penting dalam pengendalian dan koordinasi fungsi tubuh melalui integrasi yang harmonis sebagai sistem neuroendokrin. Sistem saraf, yang hanya terdapat pada hewan, terdiri atas neuron dan sel glia yang bertanggung jawab terhadap penghantaran impuls dan pengendalian fungsi tubuh. Sistem saraf pada anjing mengatur aktivitas motorik, sensorik, dan fungsi otonom untuk mendukung kelangsungan hidup. Namun, gangguan pada sistem saraf, seperti kejang, kelumpuhan, atau disorientasi, dapat disebabkan oleh berbagai faktor, termasuk kelainan bawaan, trauma, infeksi, atau penyakit degeneratif. Evaluasi diagnostik yang menyeluruh dan pendekatan penanganan yang sistematis diperlukan untuk menentukan penyebab dan terapi yang efektif. Strategi penanganan meliputi terapi medis, rehabilitasi, hingga intervensi bedah pada kasus tertentu. Studi ini bertujuan menganalisis penyakit neurologis pada anjing yang meliputi penyakit Lower Motor Neuron (LMN), Canine Distemper Virus (CDV), Rabies Virus dan strategi penanganannya untuk memberikan wawasan dalam pengelolaan kasus neurologis, mendukung kesejahteraan hewan peliharaan, dan meningkatkan kesadaran pemilik terhadap upaya preventif.